UJI EFEKTIVITAS AIR PERASAN JERUK NIPIS (Citrus aurantifolia) DAN MADU RANDU DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Propionibacterium acnes - Surya Amal, Nursalinda Kusumawati, Solikah Ana Estikomah, (Pharmaceutical Journal of Islamic Pharmacy, 2018)
Acne is one of the diseases that occurs in the skin due to inflammation caused by bacteria. Propionibacterium acnes is a main bacterium causes acne that forms part of the normal flora of the skin and only live in normal-alkaline pH. Lime juice and honey are the most commonly used by the community to overcome the problem of acne to avoid the side effects of acne medications in the form of antibiotics. Lime juice and honey have a low pH value so that it can be used as an antibacterial by inhibiting bacterial growth, even killing bacterial cells that are not acid resistant. The purpose of this study was to determine the effectiveness of lime juice and Randu honey in inhibiting the growth of Propionibacterium acnes bacteria. The study was conducted using the disk diffusion method with 4 variations of concentration; 25% v/v, 50% v/v, 75% v/v and 100% v/v in 4 repetitions incubated for 24 hours at 37 °C. The results of this study are in the form of clear zones around the disc paper which are considered as an inhibitory zones. The formation of inhibitory zones shows the potential of lime juice and honey randu (Randu honey) against the Propionibacterium acnes bacteria as antibacterial. Lime juice and Randu honey each with a concentration of 25% v/v, 50% v/v, 75% v/v and 100% v/v has the potential as an antibacterial against Propionibacterium acnes bacteria. It is concluded that the optimal concentration of lime juice and Randu honey in inhibiting the growth of Propionibacterium acnes were at a concentration of 100% v/v with a inhibition zone of 9.11 mm for lime juice and 28.10 mm for honey randu (Randu honey).